2012
DOI: 10.1097/acm.0b013e31824d5269
|View full text |Cite
|
Sign up to set email alerts
|

The Crimson Care Collaborative

Abstract: The current shortage of primary care physicians (PCPs), particularly as more individuals obtain health insurance and seek primary care services, is a growing national concern. The Crimson Care Collaborative (CCC) is a joint student-faculty initiative in post-health-care-reform Massachusetts that was started with the explicit goal of attracting medical students to primary care careers. It fills a niche for student-run clinics, providing evening access to primary care services for patients without a PCP and urge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…1 ). In total, five non-randomized controlled trials, 22 , 25 , 34 , 35 , 38 four uncontrolled before-and-after studies, 26 , 30 , 33 , 37 eight post-intervention survey or interview studies, 23 , 24 , 27 29 , 31 , 32 , 39 and one case series study 36 were included.
Figure 1 PRISMA flow diagram showing the number of records and studies identified during the search process, screened for relevance, assessed for eligibility and included in the synthesis.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 ). In total, five non-randomized controlled trials, 22 , 25 , 34 , 35 , 38 four uncontrolled before-and-after studies, 26 , 30 , 33 , 37 eight post-intervention survey or interview studies, 23 , 24 , 27 29 , 31 , 32 , 39 and one case series study 36 were included.
Figure 1 PRISMA flow diagram showing the number of records and studies identified during the search process, screened for relevance, assessed for eligibility and included in the synthesis.
…”
Section: Resultsmentioning
confidence: 99%
“…Geographically, 12 studies were performed in the USA, 22 – 24 , 26 – 28 , 30 32 , 36 38 three in the European Union, 25 , 34 , 39 and one each in Canada, 29 New Zealand, 35 and Singapore. 33 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations